Stabilizing Magnesium Hydride Complexes with Neutral Ligands - Wiesinger, Michael; Maitland, Brant; Elsen, Holger; Pahl, Jürgen; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2019)
The reaction of Mg[N(SiMe3)(2)](2) with PhSiH3 in benzene at room temperature gave a white precipitate of approximate constitution MgH1.5N ''(0.5). This undefined hydride rich Mg salt can be dissolved by addition of well-known neutral donors, such as PMDTA, DABCO or the N-heterocyclic carbene I(Me)iPr (N,N '-diisopropyl-2,3-dimethylimidazol-2-ylidine). This allowed for crystallization and structural characterization of five new magnesium hydride complexes: Mg-2(mu-H)(2)N ''(2)center dot(PMDTA) (1), Mg-4(mu-H)(6)N ''(2)center dot(PMDTA)(2) (2), Mg-5(mu-H)(7)N ''(3)center dot(PMDTA)(2) (3), Mg-2(mu-H)(2)N ''(2)center dot(DABCO)(2) (4) and Mg-2(mu-H)(2)N ''(2)center dot(I(Me)iPr)(2) (5). The PMDTA complexes 1-3 were only isolated as mixtures that could not be separated but complexes 4 and 5 have been fully characterized. The structures of the Mg hydride complexes 1, 4 and 5 are reproduced well by DFT calculations (B3PW91/6-311++G**). Bonding between Mg and hydride is largely ionic (circa 80 %) and there is very little charge transfer from the neutral donor to Mg2+. The calculated solvation enthalpies (Delta H-solv) per ligand are -12.4 kcal/mol (PMDTA), -15.9 kcal/mol (DABCO) and -20.8 kcal/mol (I(Me)iPr). In complexes 4 and 5 Bond-Critical-Points are found between the two negatively charged hydride ligands. The very high electron densities of 0.15-0.16 e/angstrom(3) in these unusual BCP's are related to the short H-center dot center dot center dot H- distances of circa 2.55 angstrom.
CRIS-Team WoS Importer:2019-10-25